AB0031 Restricted T-Cell Frequencies and Function in Patients with Rheumatoid Arthritis Revealed by a Whole Blood Stimulation Assay Using Polyclonal and Varicella Zoster Virus-Specific Stimuli. (9th June 2015) - Schub, D.; Assmann, G.; Sester, M.; Schmidt, T.
Abstract : Background: Patients with rheumatoid diseases are at increased risk for infectious complications mainly due to the immunomodulatory activity of anti-rheumatic drug treatment However, knowledge on the effect of drug-treatment on the quantity and functionality of specific cellular immune responses in rheumatic patients is limited. Objectives: To characterize the immunomodulatory effect of treatment regimens (DMARD vs biologicals) on CD4 T cells in patients with rheumatic diseases. Methods: For quantitative and qualitative T-cell analyses, 78 patients with rheumatic diseases (59 with rheumatoid arthritis (RA), 19 with seronegative spondyloarthropathies (SPA) and 39 healthy control persons were recruited. The general capacity of antigen-specific CD4 T cells was analysed after polyclonal whole blood stimulation with the superantigen Staphylococcus aureus Enterotoxin B (SEB) using intracellular staining for the cytokines IFN, IL-2, and TNF. CD127, CTLA-4 and PD1 were chosen as markers for functional anergy. Stimulation with varicella zoster virus (VZV) antigens was used for analysis of virus-specific immune responses. Results: Frequencies of SEB-reactive and VZV-specific CD4 T cells were decreased significantly in RA patients (p<0.05 and p<0.001, respectively) with median frequencies of 2.47% (IQR 2.86%) and 0.03% (IQR 0.06%) compared to healthy controls (median 3.96% (IQR 4.38%) and 0.09% (IQR 0.16%)). When stratifying results according to treatment, no differences could be observed in quantity of polyclonally stimulated T cells. In contrast, VZV-specific CD4 T-cell frequencies showed significant differences (p<0.01) with a prominent reduction in patients treated with biologicals compared to healthy controls (p<0.01). Interestingly, functional analysis revealed restricted functionality of SEB-reactive CD4 T cells especially in RA patients, demonstrated by restricted cytokine expression (mainly IFN) and increased expression of CTLA-4. PD-1 and CD127 expression as well as VZV-specific T-cell properties did not differ from those of healthy controls. Conclusions: Patients with rheumatoid arthritis have lower frequencies of antigen-specific and polyclonal CD4 T cells, which seem to be variably affected by biologicals. Together with features of functional anergy, this may predispose towards infectious complications. Future studies should address whether individual immunomonitoring may be used to guide the dosage of immunosuppressive drugs and to identify patients at risk for infection. Disclosure of Interest: None declared